2002
DOI: 10.1023/a:1019994721545
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The binding protein BiP is an endoplasmic reticulum (ER)-resident member of the HSP70 stress-related protein family, which is essential for the constitutive function of the ER. In addition to responding to a variety of environmental stimuli, plant BiP exhibits a tissue-specific regulation. We have isolated two soybean BiP genomic clones, designated gsBiP6 and gsBiP9, and different extensions of their 5' flanking sequences were fused to beta-glucuronidase (GUS) reporter gene and introduced into Nicotiana tabacu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…For the second reporter gene construct, the 1000-, 700-, and 350-bp GmNRP-B promoter fragments were excised from TOPO-pCR4 with EcoRI-SalI digestion and cloned into the pLacZi integrative vector, a URA -marked plasmid, in front of the lacZ reporter gene under the control of a minimal, inactive CYC1 (cytochrome C1) promoter, resulting in pUFV1463, pUFV1464, and pUFV1465, respectively. A 350-bp fragment of the GmBiPD promoter was obtained from the clone pUFV228 (16) by digestion with EcoRI and SalI restriction enzymes and cloned into the pLacZi vector to be used as a negative control. The resulting clone, pUFV1226, contains the lacZ reporter gene under the control of an active soyBiPD promoter (16).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the second reporter gene construct, the 1000-, 700-, and 350-bp GmNRP-B promoter fragments were excised from TOPO-pCR4 with EcoRI-SalI digestion and cloned into the pLacZi integrative vector, a URA -marked plasmid, in front of the lacZ reporter gene under the control of a minimal, inactive CYC1 (cytochrome C1) promoter, resulting in pUFV1463, pUFV1464, and pUFV1465, respectively. A 350-bp fragment of the GmBiPD promoter was obtained from the clone pUFV228 (16) by digestion with EcoRI and SalI restriction enzymes and cloned into the pLacZi vector to be used as a negative control. The resulting clone, pUFV1226, contains the lacZ reporter gene under the control of an active soyBiPD promoter (16).…”
Section: Methodsmentioning
confidence: 99%
“…A 350-bp fragment of the GmBiPD promoter was obtained from the clone pUFV228 (16) by digestion with EcoRI and SalI restriction enzymes and cloned into the pLacZi vector to be used as a negative control. The resulting clone, pUFV1226, contains the lacZ reporter gene under the control of an active soyBiPD promoter (16). …”
Section: Methodsmentioning
confidence: 99%
“…cis -elements analogous to mammalian ERSE, ERSE II and UPRE are also found in plant promoters, such as pERSE (CCAAT-N10-CACG), pUPRE (ATTGGTCCACGTCATC) and pUPRE-II (GATGACGCGTAC), and were found to be important for ER stress-induced gene expression [72,8486]. …”
Section: Unfolded Protein Response (Upr)mentioning
confidence: 99%
“…S1). In addition, UPR-responsive cis -elements (UPRE-I, UPRE-III, ERSE-I, and ERSE-II) (Buzeli et al 2002; Hayashi et al 2013; Sun et al 2013) were identified in the promoter region for all three BdBiP genes ( BdBiP1, BdBip2, and BdBip3 ; Table 1). …”
Section: Resultsmentioning
confidence: 99%